EFFECT OF NUTRISIL AND KW21+SI FERTILIZER ON Chaetoceros calcitrans GROWTH - Lestari, Ulan Ayudia; Mukhlis, Alis; Priyono, Joko (Jurnal Perikanan Unram, 2019)
The availability of natural food that meets the needs can improve the quality and quantity of seeds and ensure the sustainability of seeds production produced. One of the most important natural feeds in aquatic ecosystems is phytoplankton which is the main producer that contributes the most to the total primary water products. One type of phytoplankton commonly cultivated is Chaetoceros calcitrans. Nutrient enrichment in growing media can be done through the provision of several types of fertilizers. One type of fertilizer commonly used in phytoplankton cultivation is KW21 fertilizer. Silicate is an essential macro nutrient needed for microalgae growth in the formation of its cell walls to have high resistance to environmental stresses such as extreme conditions. One type of fertilizer that contains silicates which is a fertilizer for local products (Lombok) namely Nutrisil. The aim of the study was to determine the effect of Nutrisil fertilizer and KW21+S on growth and double time of Chaetoceros calcitrans. This study uses a completely randomized design with treatment A= concentration of Nutrisil 1,0 mL/L, B= concentration of Nutrisil 0,75 mL/L, C = concentration of Nutrisil 0,5 mL/L, D = concentration of Nutrisil 0,25 mL/L dan E = concentration of KW21 1 mL/L + Si 1 mg/L. .The data obtained were analyzed using Anova with level 5%. The results showed that the administration of Nutrisil and KW21+Si fertilizer had a significant effect on the growth of Chaetoceros calcitrans.